A Nutrient-Based Cellular Model to Characterize Acetylation-Dependent Protein-Protein Interactions - Loehr, Jérémy; Kougnassoukou Tchara, Pata-Eting; Gonthier, Kevin; Noufi, Chahinez; Linteau, Naomie; Audet-Walsh, Étienne; Lambert, Jean-Philippe (Frontiers in Molecular Biosciences, 2022)
Cellular homeostasis requires the orderly expression of thousands of transcripts. Gene expression is regulated by numerous proteins that recognize post-translational modifications—in particular, the acetylation of lysine residues (Kac) on histones. In addition to affecting the general condensation state of the chromatin, acetylated histones act as anchor points for bromodomain (BRD)-containing adapter proteins. BRDs are the primary Kac reader domains in humans, and proteins containing them act as chromatin scaffolds that organize large networks of interactions to regulate transcription. To characterize BRD-dependent interaction networks, we established cell lines in which histone acetylation is dependent on acetate supplementation. To do this, we used genome editing to knock out ATP citrate lyase (ACLY), the enzyme responsible for converting citrate to oxaloacetate and acetyl-CoA in the cytoplasm and nucleus. In our cellular model, removing acetate from the culture medium resulted in the rapid catabolism of acetylated histones to restore the nucleocytoplasmic acetyl-CoA pool. Here we report the use of our new model in functional proteomics studies to characterize BRD-dependent interaction networks on the chromatin.